Tooth-Supported overdenture retained with bareroot, coping and magnetic attachment - Surdin; Endang Wahyuningtyas; Sri Budi Barunawati; Intan Ruspita (Indonesia Prosthodontic Association, 2025)
Background : Overdenture is removable denture used to replace missing teeth and cover or rest on one or more remaining natural teeth in the mouth. Types of overdentures are non-copping abutment, abutment with copping (long, medium, short) and abutment with Attachment. Abutment with attachment overdenture can provide good retention and stabilization. Objective : The purpose of the case study is the assessment of retention improvement of overdenture dentures with coping and magnetic abutments in complete denture in the upper jaw and bareroot in complete denture in the lower jaw. Case Report : A 59-year-old woman reported having the chief complaint of difficulty in chewing food and speaking due to missing teeth in the upper and lower arch. Intraoral examination revealed the remaining teeth were 17, 23, 24, 43, and had been extruded. Tooth 23 was done to support magnetic overdenture, tooth 24 supported coping overdenture in the full maxillary denture and 43 supported bareroot overdenture in the full mandibular denture. Conclusion : Magnetic and coping retained overdenture enhance the retention in the full maxillary denture and bareroot improves the stability of the mandibular complete denture.